TATA KELOLA DANA ZAKAT, INFAQ, DAN SHODAQOH (ZIS) STUDI PADA BADAN AMIL ZAKAT NASIONAL KABUPATEN X - Lailatul Qomariyah; Muhammad Asy'ari (J-ISCAN: Journal of Islamic Accounting Research, 2022)
The large number of people in Indonesia who are Muslim encourages the implementation of islamic law in socio-economic life. One of the institutions related to this activity is an institution that manages Zakat, Infaq, and Shodaqoh (ZIS) funds. This study aims to determine the application of good amil governance in the National Amil Zakat Agency of X Regency. The research method used qualitatively using a comparative descriptive approach is used to describe the process of managing the amil zakat agency based on the decision of the chairman of the Central National Amil Zakat Agency No. 25 of 2018. This research data was obtained through documentation and interviews with a sample of five informants of the Zakat Collecting Unit. in every agency that is part of the management of zakat, infaq, and shodaqoh funds. The results of this study indicate that the National Amil Zakat Agency of X Regency has not been maximal in implementing governance on the management of zakat, infaq, and shodaqoh funds according to applicable regulations. The large number of people in Indonesia who are Muslim encourages the implementation of islamic law in socio-economic life. One of the institutions related to this activity is an institution that manages Zakat, Infaq, and Shodaqoh (ZIS) funds. This study aims to determine the application of good amil governance in the National Amil Zakat Agency of X Regency. The research method used qualitatively using a comparative descriptive approach is used to describe the process of managing the amil zakat agency based on the decision of the chairman of the Central National Amil Zakat Agency No. 25 of 2018. This research data was obtained through documentation and interviews with a sample of five informants of the Zakat Collecting Unit. in every agency that is part of the management of zakat, infaq, and shodaqoh funds. The results of this study indicate that the National Amil Zakat Agency of X Regency has not been maximal in implementing governance on the management of zakat, infaq, and shodaqoh funds according to applicable regulations.